Modulation of Ca2+ Signaling by Anti-apoptotic B-Cell Lymphoma 2 Proteins at the Endoplasmic Reticulum–Mitochondrial Interface - Vervliet, Tim; Clerix, Eva; Seitaj, Bruno; Ivanova, Hristina; Monaco, Giovanni; Bultynck, Geert (Frontiers in Oncology, 2017)
Mitochondria are important regulators of cell death and cell survival. Mitochondrial Ca2+ levels are critically involved in both of these processes. On the one hand, excessive mitochondrial Ca2+ leads to Ca2+-induced mitochondrial outer membrane permeabilization and thus apoptosis. On the other hand, mitochondria need Ca2+ in order to efficiently fuel the tricarboxylic acid cycle and maintain adequate mitochondrial bioenergetics. For obtaining this Ca2+, the mitochondria are largely dependent on close contact sites with the endoplasmic reticulum (ER), the so called mitochondria-associated membranes. There, the inositol 1,4,5-trisphosphate receptors are responsible for the Ca2+ release from the ER. It comes as no surprise that this Ca2+ release from the ER and the subsequent Ca2+ uptake at the mitochondria are finely regulated. Cancer cells often modulate ER-Ca2+ transfer to the mitochondria in order to promote cell survival and to inhibit cell death. Important regulators of these Ca2+ signals and the onset of cancer are the B-cell lymphoma 2 (Bcl-2) family of proteins. Increasing number of reports highlight the ability of these Bcl-2-protein family members to finely regulate Ca2+ transfer from ER to mitochondria both in healthy cells and in cancer. In this review, we focus on recent insights into the dynamic regulation of ER-mitochondrial Ca2+ fluxes by Bcl-2-family members and how this impacts cell survival, cell death and mitochondrial energy production.